In vivo whole-cell recording with high success rate in anaesthetized and awake mammalian brains. Issue 1 (December 2016) - Wang, Yao; Liu, Yu-zhang; Wang, Shi-yi; Wang, Zhiru
Abstract As a critical technique for dissection of synaptic and cellular mechanisms, whole-cell patch-clamp recording has become feasible for in vivo preparations including both anaesthetized and awake mammalian brains. However, compared with in vitro whole-cell recording, in vivo whole-cell recording often suffers from low success rates and high access resistance, preventing its wide application in physiological analysis of neural circuits. Here, we describe experimental procedures for achieving in vivo amphotericin B-perforated whole-cell recording as well as conventional (breakthrough) whole-cell recording from rats and mice. The success rate of perforated whole-cell recordings was 70―80 % in the hippocampus and neocortex, and access resistance was 40―70 MΩ. The success rate of conventional whole-cell recordings was ~50 % in the hippocampus, with access resistance of 20―40 MΩ. Recordings were stable, and in awake, head-fixed animals, ~50 % whole-cell patched neurons could be held for > 1 hr. The conventional whole-cell recording also permitted infusion of pharmacological agents, such as intracellular blockers of Na+ channels and NMDA receptors. These findings open new possibilities for synaptic and cellular analysis in vivo.